Comparison of Deradicalization Programs in Indonesia and India - M, Kannan; Syauqillah, Muhamad (International Journal Labs, 2025)
Terrorism is currently classified as an international crime which aims to pose a threat and fear to humanity. The presence of a deradicalization program is believed to be able to minimize and even eliminate extreme ideology which is the initial cause of acts of terrorism. Deradicalization is carried out for terrorist prisoners with the aim of eliminating extreme ideas and opening the way for terrorist prisoners to return to the basic ideology of a country and deradicalization is also carried out for society so that they can avoid extreme ideas. Each country has its own method, especially Indonesia and India, in its efforts to deradicalize terrorist convicts. However, does the deradicalization method used by Indonesia have any effect when applied to terrorist prisoners in India and vice versa. To see whether the deradicalization program between Indonesia and India has similarities, further observations are needed regarding the comparison of deradicalization programs between Indonesia and India. The method used in this research is a qualitative method whose sources are centered on literature related to the subject of discussion. The results of this research explain whether deradicalization programs in Indonesia and India have similarities and how effective these programs are in efforts to deradicalize terrorist convicts.